Development and Execution of a Virtual Learning Environment: An Approach of Library Science Students with Infoethics - Hernández Vargas, Fernando (2021)
environment (VLE), with the purpose to generate a first approach between the subject of information ethics and posgraduate students from the Library Science, Documentation and Information School (EBDI) of the National University of Costa Rica. This required primarily, the approach to the main topics of infoethics and the curricular analysis of the course entitled Professional Ethics; between the years 2015-2019, to later devise and generate an EVA using the Moodle platform, which was based on research based on design and teaching for understanding. In this way, having developed the four sessions that made up the course, one of the main results obtained was that the students expressed the need to incorporate infoethics in research processes from librarianship, both at an individual level and from their learning process in higher education.